Features of agrarian production on Ukrainian earth in the ХІХ-st century - N. P. Kovalenko (History of science and technology, 2018)
It is set that in the ХІХ-st century an agrarian production on Ukrainian earth took place in accordance with development of productive forces of society, it’s socio-economic features and scientific and technical progress and was the base on generalization of priority scientific directions and distribution of branch scientific knowledge. It was determined, that the achievements of the Ukrainian scientists from development of effective menagement found the embodiment in practice of agricultural commodity producers, both squires and separate rural owners.